Insights into the regulatory role of Plexin D1 signalling in cardiovascular development and diseases. Issue 9 (9th April 2021) - Zhang, Yi‐Fei; Zhang, Yu; Jia, Dong‐Dong; Yang, Hong‐Yu; Cheng, Meng‐Die; Zhu, Wen‐Xiu; Xin, Hui; Li, Pei‐Feng; Zhang, Yin‐Feng
Abstract: Plexin D1 (PLXND1), which was previously thought to mediate semaphorin signalling, belongs to the Plexin family of transmembrane proteins. PLXND1 cooperates mostly with the coreceptor neuropilin and participates in many aspects of axonal guidance. PLXND1 can also act as both a tumour promoter and a tumour suppressor. Emerging evidence suggests that mutations in PLXND1 or Semaphorin 3E, the canonical ligand of PLXND1, can lead to serious cardiovascular diseases, such as congenital heart defects, CHARGE syndrome and systemic sclerosis. Upon ligand binding, PLXND1 can act as a GTPase‐activating protein (GAP) and modulate integrin‐mediated cell adhesion, cytoskeletal dynamics and cell migration. These effects may play regulatory roles in the development of the cardiovascular system and disease. The cardiovascular effects of PLXND1 signalling have gradually been elucidated. PLXND1 was recently shown to detect physical forces and translate them into intracellular biochemical signals in the context of atherosclerosis. Therefore, the role of PLXND1 in cardiovascular development and diseases is gaining research interest because of its potential as a biomarker and therapeutic target. In this review, we describe the cardiac effects, vascular effects and possible molecular mechanisms of PLXND1 signalling.